ARTIFICIAL INTELLIGENCE AND THE HUMAN MIND: PSYCHOLOGICAL INSIGHTS AND IMPLICATIONS - Binoy Checkonthayil (Journal of Dharma, 2024)
Artificial intelligence (AI) is transforming industries and daily life, raising important questions about its relationship with the human mind, particularly from a psychological perspective. As AI integrates further into society, understanding its impact on human cognition, emotions and decision-making becomes particularly significant. AI technologies, such as machine learning and neural networks, mimic human cognitive functions like learning, problem-solving and decision-making, offering insights into both AI and human cognition. However, AI lacks emotional depth and ethical reasoning, emphasizing the need to embed these aspects into its development. Emotional intelligence (EI) is another critical area where AI's inability to truly understand and respond to human emotions presents challenges. The future of AI depends on designing systems aligned with psychological principles to enhance human strengths, address limitations and promote ethical outcomes. By prioritizing responsibility and inclusivity, we can create technology that complements rather than replaces human intelligence, fostering a more ethical and beneficial integration.